Handbook of physics - Benenson, Walter (Gale virtual reference library, 2002)
Provides access to information including not only the fundamental formulas of physics but also a wide variety of experimental methods used in practice. Provides information for everyday use in problem solving, homework, examinations, and practical applications of physics.